2014
DOI: 10.1016/j.bbamem.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress effect on progesterone-induced blocking factor (PIBF) binding to PIBF-receptor in lymphocytes

Abstract: Receptor-ligand binding is an essential interaction for biological function. Oxidative stress can modify receptors and/or membrane lipid dynamics, thus altering cell physiological functions. The aim of this study is to analyze how oxidative stress may alter receptor-ligand binding and lipid domain distribution in the case of progesterone-induced blocking factor/progesterone-induced blocking factor-receptor. For membrane fluidity regionalization analysis of MEC-1 lymphocytes, two-photon microscopy was used in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…However, several other shorter splice variants have been recognized with tissue-specific intra- and extra-cellular expression (255257). These short isoforms are also thought to be ligands for the PIBF receptor (256, 258). Highly proliferative cells such as trophoblast, mesenchymal stem cells, and tumor cells all express PIBF (257, 259, 260).…”
Section: P4-induced Blocking Factor (Pibf)mentioning
confidence: 99%
“…However, several other shorter splice variants have been recognized with tissue-specific intra- and extra-cellular expression (255257). These short isoforms are also thought to be ligands for the PIBF receptor (256, 258). Highly proliferative cells such as trophoblast, mesenchymal stem cells, and tumor cells all express PIBF (257, 259, 260).…”
Section: P4-induced Blocking Factor (Pibf)mentioning
confidence: 99%
“…PIBF expression has been described in several cells with a high proliferation rate [ 9 , 17 , 37 ]. It has been suggested that PIBF isoforms act as ligands implicated in the activation of proliferation signaling pathways including JAK1/STAT6 [ 9 , 10 , 12 , 38 ], through the interaction with a receptor heterocomplex consisting of PIBF-R, which is attached to the plasma membrane by a glycosylphosphatidylinositol [ 13 ], and membrane receptor IL-4R α [ 10 , 12 ]. In previous studies, PIBF (200 ng/mL) increased the number of astrocytoma cells through the activation of the IL-4R α /JAK1/STAT6 pathway [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The shorter PIBF isoforms present a tissue-specific expression and have been located in the intra- and extracellular compartments [ 9 , 10 ]. These short isoforms have been proposed as ligands of the PIBF receptor/interleukin 4 receptor α (PIBF-R/IL-4R α ) heterocomplex that activates diverse proliferative signaling pathways [ 12 , 13 ]. The most studied pathway is the IL-4R/JAK1/STAT6 [ 10 , 12 , 14 ], associated with the differentiation of Th2 cells, to produce a cytokine specific pattern [ 15 ], and with tumor cell growth [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, we and others have shown in the BALB/c mouse model that pregnancy increases lung inflammation and expression of stress-induced prostaglandins (PGs) and cyclooxygenase-2 (COX-2) prior to infection and that IAV infection enhances immunopathology in the lungs of pregnant mice relative to non-pregnant mice ( 86 88 ). Oxidative stress interferes with lipid raft clustering and has been shown to inhibit the ability of PIBF to bind its transmembrane receptor and IL-4R to induce the STAT6 signaling pathway; this interference reduces the sensitivity of cells to PIBF ( 96 , 97 ). Thus, influenza viral infection and subsequent oxidative stress may interfere with the unique lung and mucosal physiology tightly regulated by sex hormones toward successful pregnancy and fetal development.…”
Section: Introductionmentioning
confidence: 99%